Freshwater Ecosystem Policies for Sustainable Management of Eels (Anguilla spp.) in Sukabumi Regency - Siti Rahmawati; Mohammad Mukhlis Kamal; Tjahjo Tri Hartono; Robin Bahari; Triyanto Trie; Mas Davino Sayaza (Jurnal Rekayasa Lingkungan dan Biosistem, 2024)
Sukabumi Regency, rich in environmental and eel resources, faces challenges such as declining fish biodiversity, habitat degradation, and invasive species. This study used field surveys and descriptive data analysis to identify key issues in eel fisheries, including: a) low income for eel fishermen; b) limited market volume for eels; c) inadequate implementation of eel cultivation practices; d) lack of designated eel conservation areas; and e) declining eel habitat quality. To address these issues, the study proposes a sustainable eel fisheries plan with policies focused on: a) improving the eel supply chain; b) establishing and managing conservation areas; c) integrating watershed management; and d) promoting economic development for small-scale eel fishing communities.